Dectin-1-Syk-CARD9 Signaling Pathway in TB Immunity - Wagener, Matthew; Hoving, J. Claire; Ndlovu, Hlumani; Marakalala, Mohlopheni J. (Frontiers in Immunology, 2018)
One of the first steps towards mounting an effective immune response to Mycobacterium tuberculosis (Mtb) is recognition of the pathogen through Pattern Recognition Receptors (PRRs) expressed by innate immune cells. Activation of the PRR Dectin-1 by an unknown mycobacterial ligand triggers an intracellular signaling cascade involving numerous proteins, including Syk, PKCδ, and CARD9, some of which have been shown to influence host immune response to TB infection. Here we review the role of Dectin-1 signaling pathway in antimycobacterial immunity, and discuss its contribution in the control of Mtb infection, and potential applications in TB vaccine adjuvanticity.